Assessment of nutritional and lipid quality of salted cereal bars prepared with different binding agents - Tramujas,Janaína Melati (Sociedad Chilena de Nutrición, Bromatología y Toxicología, 2017)
ABSTRACT The aim of this paper was to assess the nutritional and lipid quality of salty cereal bars preparedusing different binding agents. The experiment consisted of preparing four cereal formulations with four different binding agents (collagen, guar gum, xanthan gum and psyllium). The physicochemical characteristics and main minerals of the bars were assessed to determine the nutritional value, atherogenic index and thrombogenic index. The ratios between hypocholesterolemic and hypercholesterolemic fatty acids were determined to assess the lipid quality of the product. The results show that the bars have considerable lipid content, carbohydrates, protein, fiber and energetic value. The atherogenicindexindex, thrombogenic index, and ratios between hypocholesterolemic and hypercholesterolemic fatty acids for all the formulations had good lipid quality, which indicates that the bars are a healthy food alternative.